2008
DOI: 10.1098/rsta.2008.0233
|View full text |Cite
|
Sign up to set email alerts
|

Composition and chemistry of Titan's thermosphere and ionosphere

Abstract: Titan has long been known to harbour the richest atmospheric chemistry in the Solar System. Until recently, it had been believed that complex hydrocarbons and nitriles were produced through neutral chemistry that would eventually lead to the formation of micrometre sized organic aerosols. However, recent measurements by the Cassini spacecraft are drastically changing our understanding of Titan's chemistry. The Ion and Neutral Mass Spectrometer (INMS) and the Cassini Plasma Spectrometer (CAPS) revealed an extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 36 publications
2
73
0
Order By: Relevance
“…This does not mean to say that PAHs cannot also form in Titan's atmosphere since the aromatic benzene C6H6 and its radical phenyl C6H5 are present in Titan's atmosphere (Vuitton et al, 2009a) and similar polymerization reaction paths may occur to make PAHs (Waite et al, 2007;Vuitton et al, 2007). As we have stated previously both processes could very well be occurring at the same time and heavier aerosols could be mixtures or conglomerations of fullerenes and PAHs (see comments by Thaddeus, 1994Thaddeus, , 1995 on large aerosol formation).…”
Section: Fullerenes Versus Pahsmentioning
confidence: 92%
See 1 more Smart Citation
“…This does not mean to say that PAHs cannot also form in Titan's atmosphere since the aromatic benzene C6H6 and its radical phenyl C6H5 are present in Titan's atmosphere (Vuitton et al, 2009a) and similar polymerization reaction paths may occur to make PAHs (Waite et al, 2007;Vuitton et al, 2007). As we have stated previously both processes could very well be occurring at the same time and heavier aerosols could be mixtures or conglomerations of fullerenes and PAHs (see comments by Thaddeus, 1994Thaddeus, , 1995 on large aerosol formation).…”
Section: Fullerenes Versus Pahsmentioning
confidence: 92%
“…At Titan the Cassini INMS instrument detected both acetylene (Waite et al, 2005) and benzene (Waite et al, 2007;Vuitton et al, 2009a) and their radicals C2H "Le., indirectly detected by Vuitton et al, 2009b) and C6H or phenyl by Vuitton et al (2009a). Vuitton et al (2007) also reported the detection of numerous hydrocarbons such as polyynes (C4H 2 , C611 2, C91-1 2 ), possible detection of methylpolyynes (CH 3C4H,CH3C6H) and benzene (C 61-I6).…”
Section: Introductionmentioning
confidence: 99%
“…Note that data from the Cassini/INMS (Ion and Neutral Mass Spectrometer) indicate an additional source of benzene in the ionosphere, at approximately 900 km (Waite et al 2007;Vuitton et al 2008). A general discussion of the ionospheric chemistry is presented by Vuitton et al (2009).…”
Section: Photochemistrymentioning
confidence: 99%
“…One of the surprise discoveries of Cassini/Huygens was the unexpected complexity of chemical processes that appear to be active in the outer layers of the atmosphere, the thermosphere and ionosphere, something not found in any other atmosphere in the Solar System. The paper by Vuitton et al (2009) reviews the current understanding of upper atmosphere chemistry, which is still in its infancy, and highlights the discovery of heavy neutral molecules above 1000 km altitude from in situ mass spectrometer measurements. Titan's exosphere is discussed by Dandouras et al (2009), who describe the population of energetic neutral atoms there which result from bombardment by energetic ions populating Saturn's magnetosphere.…”
mentioning
confidence: 99%